Albumin-binding caspase-cleavable prodrug that is selectively activated in radiation exposed local tumor. (July 2016) - Chung, Seung Woo; Choi, Jeong uk; Lee, Beom Seok; Byun, Julia; Jeon, Ok-Cheol; Kim, Seong Who; Kim, In-San; Kim, Sang Yoon; Byun, Youngro
Abstract: Existence of the genomically and epigenomically diverse subclones in a tumor severely limits the therapeutic efficacy of targeted agents. To overcome such a limitation, we prepared a novel targeted prodrug, EMC-DEVD-S-DOX, which comprises two important features: radiation-induced apoptosis targeting and albumin-binding properties. In particular, the prodrug binds circulating albumin after intravenous administration and then activated by caspase-3, which is upregulated from apoptotic cells that responded to radiotherapy. The prodrug was designed to bind circulating albumin to extend half-life and facilitate tumor accumulation in order to increase the possibility of contacting caspase-3, which is only transiently upregulated during apoptosis. Our results showed that EMC-DEVD-S-DOX had a prolonged half-life with enhanced tumor accumulation, which clearly benefited the therapeutic effect of the prodrug. Also, agreeing with the in vitro studies that showed ignorable cytotoxic effect in the absence of caspase-3, the prodrug was effective only when combined with radiotherapy without any noticeable systemic toxicity in vivo . Due to the highly selective action of EMC-DEVD-S-DOX independent to the complex genomic profiles of tumor, the prodrug would overcome the limitation of current targeted therapy and potentiate radiotherapy in the clinical oncology.